2018
DOI: 10.1016/j.healthpol.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a politically initiated national clinical guideline for cardiac rehabilitation in hospitals and municipalities in Denmark

Abstract: A politically initiated national clinical guideline was launched in Denmark in 2013 to improve quality and equality of cardiac rehabilitation (CR) services. The guideline is to be implemented in both hospital and community (municipality) settings due to shared responsibility for provision of CR services. Little is known about implementation outcomes of a guideline in these two settings. We aimed to study this by determining the extent to which Danish CR services in hospitals and municipalities adhered to natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
1
18
1
Order By: Relevance
“…The questionnaires were complied using the recommended national clinical guideline regarding the coverage of core CR components. A more detailed description of the survey can be found elsewhere [31]. Hospital-based questionnaires were derived from the DHRD, which collects programme-level CR data.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaires were complied using the recommended national clinical guideline regarding the coverage of core CR components. A more detailed description of the survey can be found elsewhere [31]. Hospital-based questionnaires were derived from the DHRD, which collects programme-level CR data.…”
Section: Methodsmentioning
confidence: 99%
“…lymphatic drainage) being provided by hospitals [8]. A newly published Danish study on cardiac rehabilitation demonstrated that guidelines and recommendations may have a different impact in hospitals and municipalities; municipalities were less likely to improve content of services, and demonstrated lower performance on quality aspects [9]. Thus, it is important to monitor municipality-based rehabilitation services closely.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we regard the use of data to be relatively low as only 29% of frontline staff and 50% of heads of department in the present study reported to carry out data-driven improvements based on results in the registry, and less than one in three present results to members of staff. Furthermore, in a previous study we identified gaps between evidence and practice in nearly all departments providing cardiac rehabilitation in Denmark 18…”
Section: Discussionmentioning
confidence: 99%
“…CQRs are typically introduced in clinical areas where there is a gap between evidence and practice 3. One such area is cardiac rehabilitation, which despite being an important part of secondary prevention for patients recovering from heart disease,16 is consistently reported to have evidence-practice gaps 17 18. CQRs with the purpose of monitoring and improving cardiac rehabilitation services have been established in at least seven countries 19.…”
Section: Introductionmentioning
confidence: 99%